2023
DOI: 10.1038/s42003-023-04437-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of miR-944/MMP10/AXL- axis in lymph node metastasis in tongue cancer

Abstract: Occult lymph-node metastasis is a crucial predictor of tongue cancer mortality, with an unmet need to understand the underlying mechanism. Our immunohistochemical and real-time PCR analysis of 208 tongue tumors show overexpression of Matrix Metalloproteinase, MMP10, in 86% of node-positive tongue tumors (n = 79; p < 0.00001). Additionally, global profiling for non-coding RNAs associated with node-positive tumors reveals that of the 11 significantly de-regulated miRNAs, miR-944 negatively regulates MMP10 by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Porphyromonas gingivalis is also reported to increase the invasiveness of the oral cancer cells, via induction and activation of pro‐MMP9 48 . Similar correlation is also observed in abundance of Fusobacterium and expression of MMP10 in tongue cancer, 40 a biomarker of lymph node metastases mechanistically shown to be driving invasion and migration in tongue cancer 49 . Details of the mechanistic involvement of the 2 gram‐negative opportunistic pathogens with oral cancer has been reviewed elsewhere 50,51 .…”
Section: Microbes Associated With Head and Neck Squamous Cell Carcinomamentioning
confidence: 84%
See 1 more Smart Citation
“…Porphyromonas gingivalis is also reported to increase the invasiveness of the oral cancer cells, via induction and activation of pro‐MMP9 48 . Similar correlation is also observed in abundance of Fusobacterium and expression of MMP10 in tongue cancer, 40 a biomarker of lymph node metastases mechanistically shown to be driving invasion and migration in tongue cancer 49 . Details of the mechanistic involvement of the 2 gram‐negative opportunistic pathogens with oral cancer has been reviewed elsewhere 50,51 .…”
Section: Microbes Associated With Head and Neck Squamous Cell Carcinomamentioning
confidence: 84%
“… 48 Similar correlation is also observed in abundance of Fusobacterium and expression of MMP10 in tongue cancer, 40 a biomarker of lymph node metastases mechanistically shown to be driving invasion and migration in tongue cancer. 49 Details of the mechanistic involvement of the 2 gram‐negative opportunistic pathogens with oral cancer has been reviewed elsewhere. 50 , 51 As bacteria remain the dominant species of the metagenome, the association analysis warrants a careful inspection and requires supporting biological assessment of the role of cancer associated pathogens in the cancer microenvironment.…”
Section: Microbes Associated With Head and Neck Squamous Cell Carcinomamentioning
confidence: 99%
“…AW13516 52 , AW8507 52 , NT-8e 53 , and OT9 53 , 54 head and neck cancer (HNSCC) cell lines 55 , 56 were obtained from Tata Memorial Hospital (Mumbai), while the NIH/3T3 (CRL-1658) cell line was procured from the American Type Culture Collection (ATCC). The cell lines were authenticated by DNA short tandem repeat (STR) profiling using the Promega Geneprint 10 system in conjugation with the GeneMarker HID software tool.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Dharavath et al [ 68 ] reported that miR-944 showed potential anti-metastatic activity in vivo and in vitro. They observed that miR-944 inhibited migration, invasion, and EMT of TSCC cells by targeting MMP-10.…”
Section: Mirnas As Either Tumor Suppressors or Oncomirs In Cancermentioning
confidence: 99%
“…They observed that miR-944 inhibited migration, invasion, and EMT of TSCC cells by targeting MMP-10. Hence they suggested that this miRNA could be a therapeutic target in TSCC patients [ 68 ].…”
Section: Mirnas As Either Tumor Suppressors or Oncomirs In Cancermentioning
confidence: 99%